The Influence Of Work Motivation And Work Dicipline On Employee Work Productivity Production Department In CV Nanjung Abadi Kota Tasikmalaya - Putri Mustikasari; Barin Barlian; Suci Putri Lestari (Journal of Indonesian Management, 2023)
This purpose of this study to determine the influence of work motivation and work dicipline on employee work productivity production department in CV Nanjung Abadi Kota Tasikmalaya. The method used is a quantitative method with a research sample of 41 respondents who are a production employees. The data is used primary data and secondary data. The analitytical tool in this research is path analysis using by SPSS version 25. The result showed that directly work motivation has a significant influence on work dicipline. Directly work motivation has unsignificant influence on work productivity. Directly work dicipline has a significant influence on work productivity. Undirectly work motivation has a significant influence on work productivity through work discipline.